2014
DOI: 10.1098/rsbl.2014.0193
|View full text |Cite
|
Sign up to set email alerts
|

Paradox lost: variable colour-pattern geometry is associated with differences in movement in aposematic frogs

Abstract: Aposematic signal variation is a paradox: predators are better at learning and retaining the association between conspicuousness and unprofitability when signal variation is low. Movement patterns and variable colour patterns are linked in non-aposematic species: striped patterns generate illusions of altered speed and direction when moving linearly, affecting predators' tracking ability; blotched patterns benefit instead from unpredictable pauses and random movement. We tested whether the extensive colour-pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 29 publications
1
44
0
1
Order By: Relevance
“…This interaction between environment, color pattern and behavior provides an explanation for polymorphisms in addition to the conventional ones, such as variable visual backgrounds and frequency-dependent predation (Endler 1978) or variation in inherent female preferences (Brooks and Endler 2001b;Fuller 2002). Coloration-environment interactions (Brodie 1992;Forsman and Appelqvist 1998;Calsbeek and Irschick 2007;Rojas et al 2014) may also favor the evolution of voluntary light environment preferences linked to variation in male coloration. Such correlational selection between pattern and behavior could promote either polymorphism or speciation, depending on the stability and spatial area of the environments and behavior.…”
Section: Discussionmentioning
confidence: 96%
“…This interaction between environment, color pattern and behavior provides an explanation for polymorphisms in addition to the conventional ones, such as variable visual backgrounds and frequency-dependent predation (Endler 1978) or variation in inherent female preferences (Brooks and Endler 2001b;Fuller 2002). Coloration-environment interactions (Brodie 1992;Forsman and Appelqvist 1998;Calsbeek and Irschick 2007;Rojas et al 2014) may also favor the evolution of voluntary light environment preferences linked to variation in male coloration. Such correlational selection between pattern and behavior could promote either polymorphism or speciation, depending on the stability and spatial area of the environments and behavior.…”
Section: Discussionmentioning
confidence: 96%
“…Although we observed high degrees of pattern variation on the side and ventral surfaces of frogs in our study (Figures and ), the role of this variation is unknown. Recent work in poison frogs linking patterning elements to movement behavior and detectability by predators (Barnett et al, ; Rojas, Devillechabrolle et al, ) indicates that pattern variation may be equally, or even more, biologically relevant than color variation. Further, evidence that the detectability of different color pattern variants is influenced by the existing light environment (Rojas, Rautiala, & Mappes, ) underscores the importance of incorporating information on both predator sensory abilities and ambient lighting conditions into the characterization of phenotypic variation.…”
Section: Discussionmentioning
confidence: 99%
“…; Cephalopods: Zylinski, Osorio & Shohet ; Lizards: Hawlena et al . ; Frogs: Rojas, Devillechabrolle & Endler ). For example, Allen et al .…”
Section: Discussionunclassified
“…Our comparative results coincide with focal studies that found association between pigmentation patterns and movement correlates of foraging behaviour. Rojas, Devillechabrolle & Endler () found that aposematic frogs ( Dendrobates tinctorius ) bearing elongated patterns move on average faster and more directional while foraging than individuals with interrupted patterns. Acanthodactylus beershebensis lizards that undergo ontogenetic changes in pigmentation patterns from stripes to blotches exhibit reduction in both PTM and MPM (Hawlena et al .…”
Section: Discussionmentioning
confidence: 99%